Recombinant Human Growth Hormone and Rosiglitazone for Abdominal Fat Accumulation in HIV-Infected Patients with Insulin Resistance: A Randomized, Double-Blind, Placebo-Controlled, Factorial Trial - Glesby, Marshall J. (Public Library of Science, 2013)
BACKGROUND: Recombinant human growth hormone (rhGH) reduces visceral adipose tissue (VAT) volume in HIV-infected patients but can worsen glucose homeostasis and lipoatrophy. We aimed to determine if adding rosiglitazone to rhGH would abrogate the adverse effects of rhGH on insulin sensitivity (SI) and subcutaneous adipose tissue (SAT) volume. METHODOLOGY/PRINCIPAL FINDINGS: Randomized, double-blind, placebo-controlled, multicenter trial using a 2×2 factorial design in which HIV-infected subjects with abdominal obesity and insulin resistance were randomized to rhGH 3 mg daily, rosiglitazone 4 mg twice daily, combination rhGH + rosiglitazone, or double placebo (control) for 12 weeks. The primary endpoint was change in SI by frequently sampled intravenous glucose tolerance test from entry to week 12. Body composition was assessed by whole body magnetic resonance imaging (MRI) and dual Xray absorptiometry (DEXA). Seventy-seven subjects were randomized of whom 72 initiated study drugs. Change in SI from entry to week 12 differed across the 4 arms by 1-way ANCOVA (P = 0.02); by pair-wise comparisons, only rhGH (decreasing SI; P = 0.03) differed significantly from control. Changes from entry to week 12 in fasting glucose and glucose area under the curve on 2-hour oral glucose tolerance test differed across arms (1-way ANCOVA P = 0.004), increasing in the rhGH arm relative to control. VAT decreased significantly in the rhGH arms (−17.5% in rhGH/rosiglitazone and −22.7% in rhGH) but not in the rosiglitazone alone (−2.5%) or control arms (−1.9%). SAT did not change significantly in any arm. DEXA results were consistent with the MRI data. There was no significant rhGH x rosiglitazone interaction for any body composition parameter. CONCLUSIONS/SIGNIFICANCE: The addition of rosiglitazone abrogated the adverse effects of rhGH on insulin sensitivity and glucose tolerance while not significantly modifying the lowering effect of rhGH on VAT. TRIAL REGISTRATION: Clinicaltrials.gov NCT00130286